2020
DOI: 10.3389/fneur.2020.00240
|View full text |Cite
|
Sign up to set email alerts
|

The Free and Cued Selective Reminding Test in Parkinson's Disease Mild Cognitive Impairment: Discriminative Accuracy and Neural Correlates

Abstract: Introduction: Memory alterations are common in Parkinson's disease (PD) patients but the mechanisms involved in these deficits remain poorly understood. The study aims to explore the profile of episodic memory deficits in non-demented early PD patients. Methods:We obtained neurological, cognitive and behavioral data from 114 PD patients and 41 healthy controls (HC). PD participants were grouped as normal cognition (PD-NC) and mild cognitive impairment (PD-MCI) according to the Level II criteria of the Movement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…Recent meta-analyses and lesion-based studies have also shown that verbal fluency is supported by standard language networks and underlying white-matter connectivity (Griffis et al ., 2017; Costafreda et al ., 2006; Baldo et al ., 2006). Therefore, the ERP pattern associated with lower verbal fluency – suggestive of less efficient predictive processing mechanisms, as previously dicussed – may reflect not only executive dysfunction, but also disruption in semantic networks, in line with recent findings of difficulties in temporal-dependent functions in PD and PD-MCI (Horta-Barba et al ., 2020; Martínez-Horta et al ., 2019; Lang et al ., 2019).…”
Section: Discussionsupporting
confidence: 86%
“…Recent meta-analyses and lesion-based studies have also shown that verbal fluency is supported by standard language networks and underlying white-matter connectivity (Griffis et al ., 2017; Costafreda et al ., 2006; Baldo et al ., 2006). Therefore, the ERP pattern associated with lower verbal fluency – suggestive of less efficient predictive processing mechanisms, as previously dicussed – may reflect not only executive dysfunction, but also disruption in semantic networks, in line with recent findings of difficulties in temporal-dependent functions in PD and PD-MCI (Horta-Barba et al ., 2020; Martínez-Horta et al ., 2019; Lang et al ., 2019).…”
Section: Discussionsupporting
confidence: 86%
“…Recent meta-analyses and lesion-based studies have also shown that verbal fluency is supported by standard language networks and underlying whitematter connectivity (Griffis et al, 2017;Costafreda et al, 2006;Baldo et al, 2006). Therefore, the ERP pattern associated with lower verbal fluencysuggestive of less efficient predictive processing mechanisms, as previously dicussedmay reflect not only executive dysfunction, but also disruption in semantic networks, in line with recent findings of difficulties in temporaldependent functions in PD and PD-MCI (Horta-Barba et al, 2020;Martínez-Horta et al, 2019;Lang et al, 2019).…”
Section: Pd-mci Impacts Late Semantic Processing In Predictive Contextssupporting
confidence: 76%
“…Furthermore, both executive dysfunction and damage within semantic networks may underlie these difficulties, as suggested by their association with low verbal fluency scores. Along with recent research (Horta-Barba et al, 2020;Martínez-Horta et al, 2019;Lang et al, 2019), these findings emphasize the value of examining cognitive changes in PD and PD-MCI in domains beyond executive functions, like the language domain. Interestingly, altered N400 effects are associated with a higher risk of transiting to dementia in individuals with amnesic MCI (Olichney et al, 2008).…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 57%
See 1 more Smart Citation
“…Table 2 summarizes the seven studies which employed dMRI to explore neural correlates of memory in PD (Carlesimo et al., 2012; Chung et al., 2019; Gargouri et al., 2019; Horta‐Barba et al., 2020; Wang et al., 2020; Yao et al., 2016; Zheng et al., 2014). Three of these studies did not reveal any significant relationship between measures of verbal or visual episodic memory and diffusion characteristics of the hippocampus (Chung et al., 2019; Wang et al., 2020; Yao et al., 2016).…”
Section: Discussionmentioning
confidence: 99%